Proceedings of the Evaluation and Assessment on Software Engineering 2019
DOI: 10.1145/3319008.3319031
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach for Identifying Requirement Change Management Challenges

Abstract: Requirement Change is one of the most challenging tasks in software development lifecycle, particularly in the complex context of Global Software Development (GSD). During the last decade, many studies are carried out to address these problems, however, careful examination of these works suggests that there's a potential research gap. This paper has performed a Systematic Literature Review (SLR) to identify the most significant/commonly studied challenges of requirement change management process and furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…Many systematic reviews have been conducted within the scope of GSD. Some of the most recent systematic literature reviews and mapping studies in this domain have identified solutions, challenges or research gaps in terms of software architecting, 10 knowledge sharing, 21–23 agile practices, 12,24 requirements risks and change management, 25–29 cultural differences 28,29 or process improvement, 30 and among others. Although some of these studies address aspects that could indirectly be related to GSD governance, none of them directly addresses governance issues.…”
Section: Related Workmentioning
confidence: 99%
“…Many systematic reviews have been conducted within the scope of GSD. Some of the most recent systematic literature reviews and mapping studies in this domain have identified solutions, challenges or research gaps in terms of software architecting, 10 knowledge sharing, 21–23 agile practices, 12,24 requirements risks and change management, 25–29 cultural differences 28,29 or process improvement, 30 and among others. Although some of these studies address aspects that could indirectly be related to GSD governance, none of them directly addresses governance issues.…”
Section: Related Workmentioning
confidence: 99%
“…According to Boehm [16], complexity is one of the important drivers in software cost. We combined requirements dependability and change conflicts with existing requirements which are considered as challenges in RC management in general [17] as cascading impact. Furthermore, we derived access to customer from our interview-based study findings and also adapted from Anwer et al's work [17] along with prioritization as communication is considered as a challenge in RC management in global software development and prioritization is a challenge in RC management in general, respectively.…”
Section: How Challenging Are the Requirements Changes? (Rq3)mentioning
confidence: 99%
“…Consequently, Requirements Change Management (RCM) becomes a challenging and resource-consuming activity, especially when requested multiple times in the context of GSD [15]. Additionally, due to the massive number of requirements' changes, the development organizations conduct the RCM process in an imprecise manner; thereby, significantly increasing the required amount of development cost, time, and human effort [16]- [18]. On the other hand, poor communication and coordination among the stakeholders can negatively impact the RCM process in GSD [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, poor communication and coordination among the stakeholders can negatively impact the RCM process in GSD [19], [20]. Note that poor communication mainly occurs because of inefficient knowledge sharing, geographical distance, socio-cultural differences, and temporal distances [18], [21]- [24]. As a result, develop-ment organizations need to properly manage the communication, coordination and controlling mechanisms during the RCM process.…”
Section: Introductionmentioning
confidence: 99%